Enhancing Teaching Material Development through a Digital Book Based on First Principles of Instruction - Ariani, Diana; Andinnari, Shaffiya Rasidha; Setiasih, Ratri Mei; Zulfa Anis, Anggita (Universitas Islam Negeri Raden Intan Lampung, 2026)
The rapid advancement of digital technology has fundamentally reshaped how higher education students access and engage with learning resources, particularly among digital natives who demonstrate strong preferences for interactive, multimodal, and non-linear content formats. This transformation necessitates the development of instructional materials that are not only technologically enhanced but also grounded in sound, evidence-based pedagogical frameworks. The present study aimed to design, develop, and evaluate a digital book for the Instructional Materials Development course in the Bachelor of Educational Technology program at Universitas Negeri Jakarta, Indonesia, by systematically integrating Merrill’s First Principles of Instruction (FPI) with the Rowntree development model. The development process followed three sequential and iterative stages: (1) planning, (2) preparation for writing, and (3) writing with revision. Formative evaluation was conducted by an instructional design expert, a media design expert, and 42 undergraduate students enrolled in the target course as end users. The results demonstrated high validity and practicality of the developed digital book, with overall mean scores of 4.60 from the instructional expert, 4.64 from the media expert, and 4.47 from the student trial on a five-point Likert scale. These findings indicate that the FPI-based digital book is pedagogically sound, technically robust, and strongly aligned with the learning preferences and professional needs of digital-native undergraduate students. The study contributes an empirically validated, replicable instructional design framework that integrates pedagogical theory, systematic development methodology, and empirical formative evaluation within a single development cycle, thereby advancing both the theory and practice of digital learning resource development in higher education.